2020
DOI: 10.1016/j.isci.2020.101493
|View full text |Cite
|
Sign up to set email alerts
|

HRD Complex Self-Remodeling Enables a Novel Route of Membrane Protein Retrotranslocation

Abstract: Summary ER-associated degradation (ERAD) targets misfolded ER proteins for degradation. Retrotranslocation, a key feature of ERAD, entails removal of ubiquitinated substrates into the cytosol for proteasomal destruction. Recently, it has been shown that the Hrd1 E3 ligase forms a retrotranslocation channel for luminal (ERAD-L) substrates. Conversely, our studies found that integral membrane (ERAD-M) substrates exit the ER through a distinct pathway mediated by the Dfm1 rhomboid protein. Those studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…Upon deletion of the DFM1 gene, Hrd1 levels increase and the Hrd1 complex may be remodeled, thereby enabling a novel route of membrane protein retro-translocation. This supports the functional flexibility of the Hrd1 complex in response to ER stress [ 42 , 43 ].…”
Section: Er-associated Degradation In Yeastsupporting
confidence: 66%
See 1 more Smart Citation
“…Upon deletion of the DFM1 gene, Hrd1 levels increase and the Hrd1 complex may be remodeled, thereby enabling a novel route of membrane protein retro-translocation. This supports the functional flexibility of the Hrd1 complex in response to ER stress [ 42 , 43 ].…”
Section: Er-associated Degradation In Yeastsupporting
confidence: 66%
“…During ubiquitination, Ubc6 attaches the first ubiquitin to a substrate, and Ubc7 extends ubiquitin chains using mostly lysine 48 linkages [ 56 ]. Ubiquitinated substrates are then retro-translocated to the cytosol by Cdc48/p97, which is recruited to the ER membrane by Ubx2 and/or Dfm1 [ 43 , 53 , 57 ]. The mechanism underlying the retro-translocation of membrane substrates, including Doa10 substrates, is ill-defined.…”
Section: Er-associated Degradation In Yeastmentioning
confidence: 99%
“…Remarkably, suppression of dfm1Δ alleviates proteotoxic stress by fully restoring retrotranslocation, and chromosome XV is duplicated for the sole purpose of increasing the gene dosage of HRD1 . In a recent analysis, we showed that overexpression of HRD1 allows for self-remodeling of the HRD complex, allowing Hrd1 to retrotranslocate ERAD-M substrates without Dfm1 ( Neal et al , 2020 ); in normal circumstances, ERAD-M retrotranslocation is completely dependent on Dfm1, with no involvement of Hrd1. Thus, elucidating the mechanisms of dfm1Δ suppression led to the discovery of new functions for the HRD complex and an expanded view of Hrd1’s molecular abilities.…”
Section: Resultsmentioning
confidence: 99%
“…Growth assays were carried out as described previously ( Neal et al , 2020 ). Briefly, cells were grown into log phase (OD 600 0.2–0.3) in medium with 2% dextrose.…”
Section: Methodsmentioning
confidence: 99%
“…2A,B) (Neal et al, 2018). Notably, because Hrd1 has been shown to be required for restoring retrotranslocation function when Dfm1 is absent (Neal et al, 2018(Neal et al, , 2020, our screening strain also has Hrd1 missing to prevent suppression of strains during the random mutagenesis screen. The resulting transformants were screened for high colony fluorescence due to buildup of SUS-GFP, indicating Dfm1 loss of function and inability to retrotranslocate SUS-GFP.…”
Section: Dfm1 L1 and Tm2 Mutants Are Unable To Retrotranslocate Er Membrane Substratesmentioning
confidence: 99%